Condyloma acuminatum: ts histopathological pattern - Dias, Eliane Pedra (1997)
Condyloma acuminatum is one of the clinical manifestations of papillomavirus infection. The classical histopathological features are already known and do not constitute a diagnostic problem. Clinically, it has been classified into growth or proliferative, full-expression, and regressive or persistent phases, with the histopathological aspects of these distinct phases being well documented in equine cutaneous papillomas. We have designed a protocol of histopathological analysis in order to investigate the possibility of identifying the evolutional phases in human condylomata acuminata. Sixty condylomata acuminata from the files of the Department of Pathology, Universidade Federal Fluminense, were studied regarding koilocytosis, paraceratosis, acantosis, basal cell hyperplasia and mono-nuclear cell infiltrate. After an individual analysis and comparison of the cases, the main differential aspects of condyloma acuminatum were: koilocytosis, transepithelial lymphocytic infiltrate and basal cell hyperplasia. Thus, condylomatous lesions can be histopathologically differentiated in three major patterns: proliferative, viral replication activity and regressive.